Is conciliation possible? a look at the Delimitation of Intradepartamental Political-Administrative units: case of the Municipality of Nazacara de Pacajes and its adjacent Municipality of Caquiaviri - Calla Marin, Cindy Gabriela (2023)
This work seeks to take a look at the boundary conflict in intradepartmental territorial units, the regulations that help resolve boundary conflicts and the difficulties that arise. In order to answer the main question of this work, is conciliation possible? For this purpose, the intradepartmental administrative conciliation procedure between the municipalities of Nazacara de Pacajes and Caquiaviri was considered as a case study.